Barokowy pałac we Włostowie - czy nadal jest zabytkiem? = Baroque palace in Włostów - when does a historic monument cease to be one? - Eckert, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the history of the palace-park complex in Włostów, which is registered in the register of historic buildings in the Lubuskie Province. The palace is currently in ruins, and the park has become run down and devastated. Questions therefore arise: do the relics of the palace and remains of the park continue to be historic monuments? Can the poor technical condition of the building be reason for removing it from the register?
Keywords: pałac we Włostowie; zabytki; dobro kultury; krajobraz kulturowy; palace in Włostów; historic monument; cultural object; cultural landscape